The impact of supervised physical exercise on chemokines and cytokines in recovered COVID-19 patients - Filgueira, Tayrine Ordonio; Carvalho, Paulo Roberto Cavalcanti; de Sousa Fernandes, Matheus Santos; Castoldi, Angela; Teixeira, Ana Maria; de Albuquerque, Renata Bezerra; de Lima-Filho, José Luiz; Souto, Fabrício Oliveira (Frontiers in Immunology, 2023)
COVID-19 is an infectious disease caused by the SARS-CoV-2 virus, which induces a high release of pro-inflammatory chemokines and cytokines, leading to severe systemic disorders. Further, evidence has shown that recovered COVID-19 patients still have some symptoms and disorders from COVID-19. Physical exercise can have many health benefits. It is known to be a potent regulator of the immune system, which includes frequency, intensity, duration, and supervised by a professional. Given the confinement and social isolation or hospitalization of COVID-19 patients, the population became sedentary or opted for physical exercise at home, assuming the guarantee of the beneficial effects of physical exercise and reducing exposure to SARS-CoV-2. This study aimed to investigate the effects of a supervised exercise protocol and a home-based unsupervised exercise protocol on chemokine and cytokine serum levels in recovered COVID-19 patients. This study was a prospective, parallel, two-arm clinical trial. Twenty-four patients who had moderate to severe COVID-19 concluded the intervention protocols of this study. Participants were submitted to either supervised exercise protocol at the Clinical Hospital of the Federal University of Pernambuco or home-based unsupervised exercise for 12 weeks. We analyzed serum levels of chemokines (CXCL8/IL-8, CCL5/RANTES, CXCL9/MIG, CCL2/MCP-1, and CXCL10/IP-10) and cytokines (IL-2, IL-4, IL-6, IL-10, IL-17A, TNF-α, and IFN-γ). Before the interventions, no significant differences were observed in the serum levels of chemokines and cytokines between the supervised and home-based unsupervised exercise groups. The CXCL8/IL-8 (p = 0.04), CCL2/MCP-1 (p = 0.03), and IFN-γ (p = 0.004) levels decreased after 12 weeks of supervised exercise. In parallel, an increase in IL-2 (p = 0.02), IL-6 (p = 0.03), IL-4 (p = 0.006), and IL-10 (p = 0.04) was observed after the supervised protocol compared to pre-intervention levels. No significant differences in all the chemokines and cytokines were found after 12 weeks of the home-based unsupervised exercise protocol. Given the results, the present study observed that supervised exercise was able to modulate the immune response in individuals with post-COVID-19, suggesting that supervised exercise can mitigate the inflammatory process associated with COVID-19 and its disorders. Clinical trial registration https://ensaiosclinicos.gov.br/rg/RBR-7z3kxjk, identifier U1111-1272-4730.